2001
DOI: 10.17221/7868-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Changes in serum concentration of 17 beta-estradiol in female rats during estrous cycle after treatment with atrazine and zearalenone

Abstract: A daily dose of 14 mg atrazine and 2.5 mg zearalenone, given p.o. during 5 days of estrous cycle to female rats, changed their estrous cycle in comparison with control animals. On day –1 of expected estrus, a significantly lower (p < 0.05) concentration of 17b-estradiol compared with the control group was recorded in all experimental groups of animals. In the group of animals administered zearalenone, the concentration of 17b-estradiol on the day of expected estrus was signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
(8 reference statements)
0
5
1
1
Order By: Relevance
“…In our experiment, there were no observed effects of 1.11 mg ZEN/kg diet on E2 or TS. This finding differed from those of Mitak et al (2001), who reported E2 content was increased in female rats subjected to oral ZEN administration (2.5 mg/d) during the rutting period. Berger et al (1981) reported that ZEN consumption (40 mg/kg) results in depressed plasma TS in prepubertal boars.…”
Section: Discussioncontrasting
confidence: 99%
“…In our experiment, there were no observed effects of 1.11 mg ZEN/kg diet on E2 or TS. This finding differed from those of Mitak et al (2001), who reported E2 content was increased in female rats subjected to oral ZEN administration (2.5 mg/d) during the rutting period. Berger et al (1981) reported that ZEN consumption (40 mg/kg) results in depressed plasma TS in prepubertal boars.…”
Section: Discussioncontrasting
confidence: 99%
“…(a) Each bar represents the mean ± SEM of three replicates from three independent experiments. The measured estradiol levels were within the reference range [24]. Specific calibration curves and appropriate positive/negative controls were carried out during the assay.…”
Section: Figurementioning
confidence: 99%
“…Zearalenone could induce hyperestrogenism in pigs, with typical clinical symptoms including swollen vulva ( Alexopoulos, 2001 ), vaginal prolapsed ( Blaney et al, 1984 ), as well as reproductive disorders such as infertility, miscarriage and false estrus in sows ( Etienne and Jemmali, 1982 ; Price et al, 1993 ). Notwithstanding, the effects of ZEA on endocrine disturbance, morphology and apoptosis of reproductive organs had been well established in sows ( Chang et al, 1979 ; Yang et al, 1994), experimental animals ( Milano et al, 1995 ; Kaliamurthy et al, 1997 ; Mitak et al, 2001 ) and cultured cells ( Tiemann et al, 2003 ). We found the manifest effect of ZEA on post-weaning piglets during clinical practice and therefore the studies were performed using post-weaning gilts.…”
Section: Introductionmentioning
confidence: 99%